The hot spots and frontiers of student's physical health research in China - Shilan, Li; Feng, Xiao (Universitas Pendidikan Indonesia, 2025)
The physical health of students has always attracted much attention. This study takes CNKI's core journals as the data source, uses citespace software to draw maps for visual analysis, and sorts out 506 literature under the theme of physical health of Chinese students from 1993 to the present from the aspects of annual publications, authors, institutions and keywords. The following conclusions were drawn: since 1993, the number of articles published on students' physical health has shown an increasing trend and fluctuated slightly; The number of publications published by various authors and institutions is small, no core research team has been formed, and the contacts are relatively scattered; The hot areas and frontiers of student physical health research in China mainly focus on the research on the current situation of students' physical health, the standards and evaluation of students' physical health measurement, etc. Future research hotspots may be health promotion and student physical health research analysis. It is suggested that future scholars can strengthen cross-regional cooperation and exchanges, expand research perspectives and methods, and further improve the construction of the research system, to achieve national fitness at an early date.